2013
DOI: 10.1136/bmjopen-2012-001948
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of routine prenatal iron prophylaxis and screening and treatment for anaemia: pregnancy results and preliminary birth results from a pragmatic randomised controlled trial (PROFEG) in Maputo, Mozambique

Abstract: ObjectiveTo present the pregnancy results and interim birth results of a pragmatic randomised controlled trial comparing routine iron prophylaxis with screening and treatment for anaemia during pregnancy in a setting of endemic malaria and HIV.DesignA pragmatic randomised controlled trial.SettingTwo health centres (1° de Maio and Machava) in Maputo, Mozambique, a setting of endemic malaria and high prevalence of HIV.ParticipantsPregnant women (≥18-year-olds; non-high-risk pregnancy, n=4326) attending prenatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…The birth outcomes were relatively similar in the two groups. From this pragmatic randomized controlled trial the authors concluded that routine iron prophylaxis during pregnancy did not suggest better maternal and child health (MCH) outcomes than screening and treatment for anemia in a setting of endemic malaria and HIV 87 .…”
Section: Management Of Anemia In Pregnancy Weekly Iron and Folic Acidmentioning
confidence: 99%
“…The birth outcomes were relatively similar in the two groups. From this pragmatic randomized controlled trial the authors concluded that routine iron prophylaxis during pregnancy did not suggest better maternal and child health (MCH) outcomes than screening and treatment for anemia in a setting of endemic malaria and HIV 87 .…”
Section: Management Of Anemia In Pregnancy Weekly Iron and Folic Acidmentioning
confidence: 99%
“…Moreover, the usual definition of PPH (blood loss ≥500 mL during vaginal delivery and ≥1000 mL during cesarean section) may not be clinically relevant in sub‐Saharan Africa, where small amounts of blood loss may have detrimental outcomes in patients with preexisting severe (hemoglobin <7 g/d) or moderate anemia (hemoglobin 7‐9.9 g/d). Although never formally studied, this is important to note, since the prevalence of maternal anemia approaches 80% in some countries, compared to approximately 5% in the United States . Additionally, there is clinical evidence that anemia can increase the risk of surgical bleeding and PPH …”
Section: Introductionmentioning
confidence: 99%
“…The details of the PROFEG Trial have been described elsewhere (13,16) . The trial was designed as a pragmatic randomized trial comparing two Fe administration policies on maternal and child health in two health centres (1 o de Maio and Machava) in Maputo: routine Fe (Fe prophylaxis from the first to the last prenatal visit) v. selective Fe (screening and treatment for anaemia).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…routine Fe supplementation from the first prenatal visit until delivery) v. selective Fe prophylaxis (i.e. screening for anaemia and Fe supplementation only to those found to be anaemic) during pregnancy (13,16) . Pragmatic trials are useful for comparing and informing choices between different treatment policies and are more suitable to study effects in normal clinical practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation